Measuring the Difficulties of Early Adulthood: The Development of the Quarter Life Crisis Scale - Afandi, Muslim; Afandi, Nail Hidaya; Afandi, Syed Agung; Erdayani, Rizki (Jurnal Kajian Bimbingan dan Konseling, 2024)
This study was conducted to develop a quarter-life crisis scale that can be used to measure the quarter-life crisis of early adulthood in Indonesia. Although it has begun to become a concern for researchers in Indonesia, the development of the quarter-life crisis scale has never been created. Some researchers have adapted the constructs developed by foreign researchers, which are not necessarily suitable for applicated in Indonesia. The development of this scale goes through 5 stages: conceptualization of the test; test construction; test trial; item analysis; and test revision. The test trial was filled by 181 early adults in Indonesia from Pekanbaru, Malang, Medan, Padang, Batam, Madura, Lombok, Pangkalan Kerinci, Solo, Surabaya, Jakarta, Bogor, and Yogyakarta. The results showed that there are 26 valid and consistent items that can be used to measure the early adult quarter-life crisis in Indonesia, which is indicated by the validity of the rcount greater than rtable and the Cronbach Alpha value of 0.854.